Calidad microbiológica, físico-química y organoléptica del hongo comestible (pleurotus ostreatus) fresco y deshidratado, cultivados en tres residuos de cosecha - Cortéz Salazar, Tanya Maribel (2016)
This research aimed to analyze the microbiological, physico-chemical and organoleptic quality of the edible fungus Pleurotus ostreatus fresh and dehydrated, grown in three crop residues. An experimental design was applied completely random within a bifactorial arrangement 3 x 2 (Factor A = Residual shell slacker (Cajanus cajan), Waste shell shells aged beans (Phaseolus vulgaris) and Pseudostem banana (Musa paradisiaca) factor B = Mushrooms Fresh and Dried), with four repetitions and to determine differences between treatments the multiple range test of Tukey (p <0.05) was used, according to the variables physicochemical analysis of edible fungus Pleurotus ostreatus, it was determined that the use of different substrates, causes a variation between treatments in the nutritional composition, especially in the moisture content, dry matter, ash and pH on the content of fiber and protein T4 and T6 were those that excelled, being T1 which showed lower 0.76% fat percentage. By employing the method of dehydration, samples, showed that there is variation in the nutritional composition due to the applied manufacturing process. In the microbiological testing, the substrates used and the method of dehydration do not affect the bioburden (Mesophiles, E. coli, molds and yeasts) of edible fungus, the reported values are within allowable ranges established by the Health Standard 007- 98-SA and the Central American Technical Regulations. The presence of microorganisms is due to external factors. Organoleptic assessment for all treatments obtained acceptability of 4 for edible fungus. It was shown that the type of agro-industrial waste used had no significant effect on the color, aroma and flavor as indicated by the results of the sensory analysis.